Relative importance of soil properties and microbial community for soil functionality: insights from a microbial swap experiment. (25th May 2016) - Delgado‐Baquerizo, Manuel; Grinyer, Jasmine; Reich, Peter B.; Singh, Brajesh K.
Summary: The most accepted theories in soil ecology suggest that broad (e.g. respiration) and specialized (e.g. denitrification) functions are affected differently by resource availability and microbial communities in terrestrial ecosystems. However, there is a lack of experimental approaches quantifying and separating the role of microbial communities from the effect of soil abiotic properties on different aspects of soil ecosystem functionality. Here, we conducted a full‐factorial design microcosm experiment and used random forest and structural equation modelling (SEM) analyses to evaluate the role and the relative importance of soil properties (sterile soils A, B and C differing in abiotic attributes) and microbial communities (microbial inoculums from soils A, B and C) in driving soil respiration (i.e. broad functioning), denitrification (i.e. specialized functioning) and four enzyme activities and carbon (C) and nitrogen (N) availability in soil. Soils with the higher total C (soils B and C) promoted the highest soil C and N availability, enzyme activities and broad functioning (i.e. soil respiration); however, we did not find any effect of total C on specialized functions (i.e. denitrification rates). Random forest analyses showed that both soil properties (i.e. total C and pH) and microbial abundance determined broad functioning (i.e. soil respiration), as well as the production of enzyme activities, and C and N availability in soil. However, we found that microbial communities were more important than soil properties for modulating specialized functioning (i.e. denitrification rates) in soil environments. Finally, our SEM also indicated that broad functioning, which is widely distributed across living organisms, is limited by both resource availability and microbial abundance. Furthermore, specialized functioning, which is conducted by particular groups of organisms, may be highly sensitive to changes in the microbial community. Overall, our findings provide direct experimental evidence for the relative importance of soil properties and microbial communities on broad and specialized functioning. Such evidence helps advance our understanding of different drivers of soil ecosystem functioning which will be crucial to developing an ecologically relevant theory about below‐ground ecosystem functioning. A lay summary is available for this article. Abstract : Lay Summary